Integrative management of insomnia during cancer chemotherapy: A case report - P. Arathi; K. Sreejith; K. Pavithran; Devipriya Soman (Journal of Ayurveda and Integrative Medicine, 2024)
Introduction: Insomnia is common among cancer patients, affecting about 50% undergoing cancer treatment. Insomnia can be due to various reasons, such as physical-pain, psychological-distress and medication side-effects. Insomnia has significant impact on quality of life of cancer patients. Even-though managed with hypnotics and antipsychotic drugs, they cause dependency with various short-term and long-term complications. Presenting a case throwing light on Ayurveda topical intervention as add-on to standard-of-care in insomnia during cancer chemotherapy. Method: A 51-year-old female patient with breast-cancer with extensive necrosis extending to subcutaneous areas was due for second cycle chemotherapy and was diagnosed with moderate-insomnia with a score of 21 as per Insomnia Severity Index in the Out-Patient-Department. Quality of sleep was assessed using Pittsburgh-Sleep-Quality-Index. Treated for 14 days during the break between cycle two and cycle three with Shirothalam (applied on the vertex) using Kachuradi Churnam with Kshirabala 101 and Padabhyangam (foot massage) using Kshirabala thailam as add-on to Tab Zolpidem5mg. Assessment was conducted on baseline and after 14 days of intervention. Results: Assessment for insomnia before and after intervention was conducted with Insomnia-Severity-Index. The score improved from 21 to 2. Quality of sleep before and after intervention was assessed using global PSQI. It improved from 20 to 8. Discussion: In Ayurveda, Nidranasam (loss of sleep) results from aggravation of Vata-Pitta (body humors responsible for movement and cognition and digestion, metabolism and heat of body), depletion of Kapha (body humor responsible for structural cohesion of body), derangement of Manasika-Dosa (mental constituents) and other diseases. All these etiological factors are attributed by Tikshna(sharp)- Uṣhna(hot potency) and Ruksha(dry) chemotherapy regimens. Vata-Pitta-hara (normalising Vata and Pitta) and Indriyaprasadaka (clearing senses) action of medicines used could induce sleep and effectively improve quality of sleep. Conclusion: Integrative-intervention was found to be beneficial in improving insomnia and quality of sleep without any reported complications or dependency in this case. After 14 days of ayurvedic intervention, the patient could get sleep even without taking zolpidem 5mg and external therapies. Same protocol could be considered for generalization so that it could modify or reduce usage of hypnotics and antipsychotic-drugs.